Methicillin-Resistant Staphylococcus aureus (MRSA) in Dairy Products and Bulk-Tank Milk (BTM) - Camino González-Machado; Rosa Capita; Carlos Alonso-Calleja (MDPI AG, 2024)
In order to contribute to an assessment of the role of food in the risks of transmission of methicillin-resistant Staphylococcus aureus (MRSA), a review was undertaken of research on this microorganism in milk and dairy products published from January 2001 to February 2024. A total of 186 publications were selected, 125 for dairy products and 61 for bulk-tank milk (BTM). MRSA was detected in 68.8% of the research into dairy products and 73.8% of investigations relating to BTM, although in most studies the prevalence was less than 5%. Of the set of S. aureus strains isolated, approximately 30% corresponded to MRSA. The foods most extensively contaminated with this microorganism were raw milk and some types of soft cheese. Determination of the mecA gene on its own is known not to suffice for the detection of all MRSA strains. The great diversity of techniques used to study MRSA in milk and dairy products made it difficult to draw comparisons between studies. It would thus be advisable to develop a standardized protocol for the study of this microorganism in foods.